(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Tourism is a significant development driver for financial and social development, job creation, and poverty alleviation. It also has a significant responsibility to contribute in encouraging the state’s economic development to be quicker, more sustainable, and more inclusive. India has the most diverse terrain and climate, allowing a diverse variety of plants and animals to thrive. Including its very old cultural history, a plethora of landmarks, and nature’s bounty, Odisha epitomizes a thriving tourist industry. Zoos have long been popular meeting places for families and friends, and many individuals find psychological solace in taking in the natural environment and engaging with animals. Zoo visitors come to the zoo with a diverse set of motivations, interests, and knowledge about animal conservation and environmental problems. The main goal of this study is to determine the degree of satisfaction of zoological park visitors at Nandankanan based on several factors such as communication, visibility, and information availability. From September to December 2016, data was gathered from 250 visitors in a random sample utilizing structured questionnaires. The majority of tourists are pleased with communication facilities, information availability, and enclosure, visibility, and guide services. To fulfil the overall level of satisfaction of tourists, the lot of wildlife, exhibition services, leisure facilities, and other amenities need to be improved.